Development of a Scandinavian winter oat by molecular breeding and tissue culture techniques - Jonsson, Rickard; Gharti-Chhetri, Gokarna; Bräutigam, Marcus; Jonsson, Anders; Olsson, Olof (MTT, 2004)
During the winter 2002/2003, 174 different oat cultivars were planted in the field of Landskrona, Sweden to identify cold hardy lines. The germplasm represented the best winter hardy oats available in the world, originating from seed collections in the US (USDA-NSGC), the Vavilov Institute in St Petersburg, Lochow-Petkus in Germany and IGER in Great Britain. Spring oat (Belinda) and winter barley (SW Hampus) were also included in the trial as references. Weather data was continuously monitored. In December, triplicates of all field-grown lines were established in the green house from field selections. In January, a second batch of plants of the most promising accessions was collected in the field. Parameters like vigour, time of flowering and height of plants at bolting were recorded. Some of the lines were also established in tissue culture. Due to the severe winter in south Sweden in 2003, all plants except the repeats from one single line died. This surviving line came from the Pennsylvania winter oat-breeding program and was denoted as Pen#65. Pen#65 plants were crossed with German winter oats and segregating F2 populations will be tested in field trials during the coming winters. During the winter 2003/2004 a second field trial on winter oat was done. In this trial, leaf samples from several individual plants were collected at different time and temperature intervals. Total RNA was extracted, and global expression studies were performed by micro-arrays using an oat biochip of 2866 different genes, developed by us. From these studies key genes up- and down regulated in the field during winter stress conditions are identified. This information will be used to develop new molecular markers for an efficient selection of cold tolerant oat varieties in segregating breeding populations. Work is also in progress to establish an Agrobacterium mediated genetic transformation protocol for the Pen#65 line. Key genes, will then be introduced to the Pen#65 line by genetic transformation.
Keywords: Ka; winter oat; field test